2016
DOI: 10.5125/jkaoms.2016.42.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Management of maxillofacial injuries in bear mauling cases: a review of 20 cases

Abstract: Objectives As the craniofacial and neck regions are prime areas of injury in bear attacks, the careful management of soft and hard tissue injuries and selection of reconstructive options is of the utmost importance. This study will review the incidence and patterns of bear mauling in eastern India reported to our department and the various modalities used for their treatment over a period of 7 years. It also documents the risks of infection in bear mauling cases and the complications that have occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Tissue loss requires loco-regional or free flaps depending on the availability of the tissue and reconstructive needs. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Tissue loss requires loco-regional or free flaps depending on the availability of the tissue and reconstructive needs. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…3 Complex surgical repairs, including reconstruction with skin flaps or skin grafts, are required in 25% of patients presenting with craniofacial injuries. 23 Bear attack victims may present with extremity fractures as well. Upper extremity injuries (notably humerus, clavicle, and forearm fractures) are more common than lower extremity injuries, 27 particularly when victims protect their face with their arms.…”
Section: Discussionmentioning
confidence: 99%
“…11 In contrast one study reported no surgical site infections in any patients. 13 In a study found that 41% out of 58 victims reported serious head injuries and 5% of the victims to the fatal injuries leading to death. 8 In present study overall mortality was found to be 2% due to head injury.…”
Section: Complicationsmentioning
confidence: 99%